Dispute Resolution Methods, Fundamental or Human Rights and Legal Pluralism - Damiani di Vergada Franzetti, Enrico (SocietàMutamentoPolitica, 2023)
The analysis of modern political-institutional systems, democratic-constitutional of a liberal mold, if it clarifies the reasons for the presence and diffusion of dispute resolution methods (state awards), of fundamental and human rights (general) attributable to the new elites of power and government, therefore to the bourgeois class, in the context of a monistic and statistic conception of legal systems, then does not explain the reasons for the diffusion and progressive multiplication of alternative methods of resolving disputes, such as fundamental or human rights in more recent eras. It is therefore necessary to analyze the processes of change that have affected the State, the law, the judicial systems, therefore the fundamental and human rights and the methods of resolving disputes in the light of the phenomenon of legal pluralism.